Forest Working Plans - some Suggestions to Make them Effective - Maslekar, A. R. (Indian Forester, 1993)
The Working Plan is a written document of planning and has been the basis of scientific forest management for over a century. Over the last few decades, various factors, such as developmental planning, industrial expansion, and population growth, have seriously affected forest working and forest protection. In that context conventional Working Plans have lost their role to a large extent. Working Plans have to be strengthened to make them more effective.